INSTITUTIONAL THEORY: A BIBLIOMETRIC STUDY OF LAST DECADE IN THE WEB OF SCIENCE - Motke, Francies Diego; Ravanello, Felipe da Silva; Rodrigues, Glauco Oliveira (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
The objective of this study is to analyze the characteristics of publications related to the Institutional Theory from 2005 to 2014. For this, we used the base Web of Science ISI Web of Knowledge seeking to identify the main subject areas, authors, institutions, title of sources, countries, languages and years of these publications. In addition, threads 20 have been related to this Institutional Theory for calculating the index HB, identification index I of hot topics, according to the methodology Banks (2006). The results show that the highest number of publication lies with the authors Lai and Wright, mostly published in the Journal of Business Ethics, especially the institution University of Nottingham, mainly concentrated in the United States and in English. It was identified that Institutional changes, Strategy, Entrepreneurship, Innovation, Agency Theory, Emerging economies, Government and Resourses-based Theory are hot topics related to Institutional Theory. By comparing the most cited articles to the authors with the most publications identified that Sarkis, Meyer, Marquis, Zhu and Dacin can be considered as references studies that address the Institutional Theory.